The roles of attachment and resilience in perceived stress in medical students - Galilee Thompson (Canadian Medical Education Journal, 2018)
Background: Medical students are susceptible to high levels of psychological stress, while being equipped with lower levels of resilience, especially females. Adult attachment is a known risk factor for a broad range of mental health difficulties and poor coping. The purpose of this study is to examine relationship attachment style, perceived stress, and resilience in medical students. Methods: Data was collected via an online survey using self-report measures from University of Saskatchewan undergraduate medical students (n = 188). Attachment was assessed with the Relationship Questionnaire and Experiences in Close Relationships Scale. Resilience and stress were assessed with the Connor-Davidson Resilience Scale and Perceived Stress Scale, respectively. Results: Approximately half of our sample endorsed secure attachment style (49.4%). Females reported significantly more attachment insecurity, higher attachment anxiety, higher perceived stress, and lower resilience compared to males, as expected. As predicted, attachment anxiety and avoidance were predictors of perceived stress. Mediation analyses supported the hypothesis that resilience acted as a partial mediator between attachment insecurity and perceived stress. Conclusion: These findings suggest attachment plays a role in perceived stress in medical students. In addition, the role of resiliency in protecting against this effect highlights potential areas for intervention to improve medical student well-being and provides a foundation for longitudinal follow-up.